2004
DOI: 10.1523/jneurosci.3649-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Roles of Axon-Schwann Cell Interactions

Abstract: Schwann cells (SCs) cover most of the surface of all axons in peripheral nerves. Axons and these glial cells are not only in intimate physical contact but also in constant and dynamic communication, each one influencing and regulating the development, function, and maintenance of the other. In recent years, there has been significant progress in the understanding of the molecular mechanisms of axon-Schwann cell interactions, particularly those relevant for postnatal development and maintenance of nerve functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 139 publications
(140 reference statements)
6
130
1
7
Order By: Relevance
“…In the center of Drosophila peripheral nerves, the WG embed axons in bundles or individually within single membrane wraps, similar to the non-myelinating Schwann cells of vertebrate peripheral nerves (Corfas et al, 2004). Our results show that WG predominantly express PS3 and PS integrin subunits in complexes positive for Ilk and Talin along the WG membrane.…”
Section: Ps Integrin Is Required To Maintain Wrapping Glia Ensheathmsupporting
confidence: 54%
“…In the center of Drosophila peripheral nerves, the WG embed axons in bundles or individually within single membrane wraps, similar to the non-myelinating Schwann cells of vertebrate peripheral nerves (Corfas et al, 2004). Our results show that WG predominantly express PS3 and PS integrin subunits in complexes positive for Ilk and Talin along the WG membrane.…”
Section: Ps Integrin Is Required To Maintain Wrapping Glia Ensheathmsupporting
confidence: 54%
“…The expression of the GFAP, CD44 (Fig. 1B, F) and NGF-R (data not shown) indicated that this cell line expressed important molecules that are characteristic of non-myelinating SC (Corfas et al 2004). Even though ST88-14 cells presented a non-myelinating phenotype, a low level of MBP was detected in these cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Thus, while axonal signals regulate myelin production, myelin, synthetized by Schwann cells, regulates axonal diameter, formation of the nodes of Ranvier and nerve conduction velocity. 1 In this context, overexpression of a therapeutic protein by the appropriate cell type may be crucial to maintain or enhance both, the crosstalk between different cell types and the PNS function.…”
Section: Introductionmentioning
confidence: 99%